Microwear textures associated with experimental near-natural diets suggest that seeds and hard insect body parts cause high enamel surface complexity in small mammals - Winkler, Daniela E.; Clauss, Marcus; Kubo, Mugino O.; Schulz-Kornas, Ellen; Kaiser, Thomas M.; Tschudin, Anja; De Cuyper, Annelies; Kubo, Tai; Tütken, Thomas (Frontiers in Ecology and Evolution, 2022)
In mammals, complex dental microwear textures (DMT) representing differently sized and shaped enamel lesions overlaying each other have traditionally been associated with the seeds and kernels in frugivorous diets, as well as with sclerotized insect cuticles. Recently, this notion has been challenged by field observations as well as in vitro experimental data. It remains unclear to what extent each food item contributes to the complexity level and is reflected by the surface texture of the respective tooth position along the molar tooth row. To clarify the potential of seeds and other abrasive dietary items to cause complex microwear textures, we conducted a controlled feeding experiment with rats. Six individuals each received either a vegetable mix, a fruit mix, a seed mix, whole crickets, whole black soldier fly larvae, or whole daychicks. These diets were subjected to material testing to obtain mechanical properties, such as Young’s modulus, yield strength, and food hardness (as indicated by texture profile analysis [TPA] tests). Seeds and crickets caused the highest surface complexity. The fruit mix, seed mix, and crickets caused deepest wear features. Moreover, several diets resulted in an increasing wear gradient from the first to the second molar, suggesting that increasing bite force along the tooth row affects dental wear in rats on these diets. Mechanical properties of the diets showed different correlations with DMT obtained for the first and second molar. While first molar wear was more correlated to maximum TPA hardness, second molar wear was more strongly correlated to maximum yield stress and maximum TPA hardness. This indicates a complex relationship between chewing mechanics, food mechanical properties and observed DMT. Our results show that in rats, seeds are a main cause of complex microwear textures, but that hard insect body-parts can also cause complex microwear textures. However, the similarity in parameter values of surface textures resulting from seed and cricket consumption did not allow for differentiation between these two diets in our experimental approach.